Antibacterial potential of restorative materialsagainst cariogenic species - Oliveira, Naiara Araújo de (2017)
Objective: To determine the antibacterial potential of five restorative materials against microorganisms associated with caries process: Streptococcus mutans, Lactobacillus casei and Bifidobacterium dentium. Methods: The antibacterial effect of five different restorative materials were evaluated in this study: Fuji IX Extra, Fuji II LC, Ion-Z, Beautifil II and Filtek Z250XT using two methodologies: agar diffusion and direct contact tests. Glass ionomer cements (GIC) were used immediately or 10 minutes after manipulation. For the agar test the mean inhibition zones in millimeter (mm) were measured, and for the direct contact test the number of colony forming units was evaluated by scores. Results: Fuji IX Extra presented the greatest mean inhibition zone (14,00 mm) for L. casei, and Ion-Z immediately after manipulation showed inhibition zones for all three bacteria tested. At the direct contact test, S. mutans was the most resistant bacteria with dense bacterial growth, and B. dentium demonstrated lower resistance against the materials tested. Conclusions: Considering the methodology used and result analysis, conventional Glass Ionomer Cements presented better results than resinous materials, and the finding varied according tested bacteria.